2014
DOI: 10.1186/1878-5085-5-10
|View full text |Cite
|
Sign up to set email alerts
|

The review of innovative integration of Kampo medicine and Western medicine as personalized medicine at the first multidisciplinary pain center in Japan

Abstract: BackgroundThe Japanese medical system is unique because it is the only country in the world where Western medicine and traditional Japanese medicine including Kampo medicine, traditional Japanese herbal medicine, are used in our daily clinical practice. Pain is essentially an interactive psychophysiological behavior pattern. Thus, an interdisciplinary approach is often recommended in providing appropriate therapeutic care for the patients suffering from chronic and intractable pain. In addition, we have been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…In the absence of an organic disease, KM can successfully balance qi‐blood‐fluid and/or heat‐cold condition, which is conceptually different from Western medical practices. Arai et al reported that Kampo prescription to manage psychological symptoms such as yokukansan, kamishoyosan, and kososan was used for psychopathological patients suffering from chronic pain in a multidisciplinary pain center . For example, yokukansan can influence several neurotransmitters and receptors such as serotonergic and glutamate receptors, which can provide a significant degree of control over the entire body.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an organic disease, KM can successfully balance qi‐blood‐fluid and/or heat‐cold condition, which is conceptually different from Western medical practices. Arai et al reported that Kampo prescription to manage psychological symptoms such as yokukansan, kamishoyosan, and kososan was used for psychopathological patients suffering from chronic pain in a multidisciplinary pain center . For example, yokukansan can influence several neurotransmitters and receptors such as serotonergic and glutamate receptors, which can provide a significant degree of control over the entire body.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Nijutsuto is a Kampo formula used to effectively treat frozen shoulder. [8][9][10] We have prescribed Nijutsuto for almost all patients with frozen shoulder refractory to Western medical treatment in our clinical daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Nijutsuto (ingredients: white and blue atractylodes, hoelen, citrus, arisaema, cyperus, scute, clematis, chianghuo, pinellia, liquorice, ginger) has been a Kampo formula used to effectively treat frozen shoulder. [8][9][10] We report here that Nijutsuto combined with a 20-minute exercise program improved pain intensity and shoulder function in 13 patients with frozen shoulder refractory to Western medical treatment.…”
mentioning
confidence: 99%
“…The Japanese government had long recognized Kampo, even as Kampo herbs were categorized as drugs separate from Western synthetic drugs. It took several more years for Kampo medicine to receive official attention around 1970 [1][2][3]. The time-tested herbal remedies of Kampo had regained the attention of the public at last.…”
mentioning
confidence: 99%